Treatment of climacteric disorders in menopause - V.E. Radzinskiy; I.M. Ordiyants (LCC «Medicine-Inform», 2018)
Treatment of climacteric disorders in menopause Radzinsky V.E., Ordiyants I.M. Peoples' Friendship University of Russia, Moscow The onset of menopause is one of the most critical periods in a woman's life. Climacteric syndrome (CS) develops in 65-80% of women as a result of physiological deficiency of estrogens. The most frequent phenomena, associated with the age-related insufficiency of female sex hormones, include disorders from the autonomic nervous system, emotional disorders, atrophic changes in the vaginal wall, skin and mucous membranes, resulting in urogenital chronic inflammatory diseases, dermatitis. These disorders are the decisive factor in the prescription of drugs for CS treatment. The main direction of therapeutic and preventive work is a comprehensive correction of hormone-deficient conditions based on menopausal hormone therapy. However, this therapy can be contraindicative for women with various diseases, such as estrogen-dependent oncological diseases or thrombosis in the anamnesis. In this connection, the so-called «alternative» therapies (selective modulators  of estrogen receptors, phytoestrogens, neuropeptide vasomotor blockers) are used. The use of neuropeptide vasomotor blockers showed a confirmed positive effect in the treatment of clinical manifestations of CS. Pineamin®, created by synthesis of  a complex of epiphysis polypeptides, is one of such drugs. Pineamin® is a non - toxic drug, which quickly stops neurovegetative symptoms of CS. Key words: climacteric syndrome, menopause, estrogen deficiency, phytoestrogens, neuropeptide vasomotor blockers, Pineamin. For citation: Radzinsky V.E., Ordiyants I.M. Treatment of climacteric disorders in menopause // RMJ. 2018. № 5(I). P.37 -40.